Targeting TWIST1 through loss of function inhibits tumorigenicity of human glioblastoma. Issue 7 (29th May 2018) - Mikheev, Andrei M.; Mikheeva, Svetlana A.; Severs, Liza J.; Funk, Cory C.; Huang, Lei; McFaline‐Figueroa, José L.; Schwensen, Jeanette; Trapnell, Cole; Price, Nathan D.; Wong, Stephen; Rostomily, Robert C.
Abstract : TWIST1 (TW) is a bHLH transcription factor (TF) and master regulator of the epithelial‐to‐mesenchymal transition (EMT). In vitro, TW promotes mesenchymal change, invasion, and self‐renewal in glioblastoma (GBM) cells. However, the potential therapeutic relevance of TW has not been established through loss‐of‐function studies in human GBM cell xenograft models. The effects of TW loss of function (gene editing and knockdown) on inhibition of tumorigenicity of U87MG and GBM4 glioma stem cells were tested in orthotopic xenograft models and conditional knockdown in established flank xenograft tumors. RNAseq and the analysis of tumors investigated putative TW‐associated mechanisms. Multiple bioinformatic tools revealed significant alteration of ECM, membrane receptors, signaling transduction kinases, and cytoskeleton dynamics leading to identification of PI3K/AKT signaling. We experimentally show alteration of AKT activity and periostin (POSTN) expression in vivo and/or in vitro . For the first time, we show that effect of TW knockout inhibits AKT activity in U87MG cells in vivo independent of PTEN mutation. The clinical relevance of TW and candidate mechanisms was established by analysis of the TCGA and ENCODE databases. TW expression was associated with decreased patient survival and LASSO regression analysis identified POSTN as one of top targets of TW in human GBM. While we previously demonstrated the role of TW in promoting EMT and invasion of glioma cells, these studies provide direct experimental evidence supporting protumorigenic role of TW independent of invasion in vivo and the therapeutic relevance of targeting TW in human GBM. Further, the role of TW driving POSTN expression and AKT signaling suggests actionable targets, which could be leveraged to mitigate the oncogenic effects of TW in GBM. Abstract : We demonstrate that TWIST1 knockdown inhibits glioma stem cell tumorigenicity through activation of apoptosis, inhibition of periostin expression and AKT activity. TW knockdown in glioma stem cells decreased the number of viable cells with corresponding increases on activated caspase 3+ tumor cells compared to controls. Reduced tumorigenic phenotype in cells with TW knockdown was completely reversed by re‐expression of exogenous TW and correlated with reduced active caspase 3 expression, activation of periostin expression and AKT activity. The role of TW driving POSTN expression and AKT signaling suggests actionable targets, which could be leveraged to mitigate the oncogenic effects of TW in GBM.